Efektivitas Pemberian Nugget Baby Crab dan Kacang Hijau terhadap Kadar IGF-1, Albumin, Seng, dan Hemoglobin Darah pada Remaja Pra-Menarche: Effectiveness of Baby Crab and Mung Bean Nuggets on Blood IGF-1, Albumin, Zinc, and Haemoglobin Levels in Pre-Menarche Adolescents - Siahaan, Ginta; Nainggolan, Efendi; Sitepu, Yunki Alwina Br; Hutauruk, Grace Natalia Putri; Veronica, Gloria Agustini (Amerta Nutrition, 2025)
Background: The pre-menarche phase is a transition period from childhood to adolescence. The period of early preparation for an adolescent girl towards self-maturation and maturation of reproductive cells. The pre-menarche period requires nutrients, for the growth and development process. Nugget is a snack food that is favored by all age groups, can be made from fish, crabs, nuts and eggs that are easy to obtain. Objectives: To analyze the effectiveness of baby crab and mung bean (BC Cangi) nuggets on IGF-1, albumin, zinc and hemoglobin levels in pre-menarche adolescents. Methods: Type of quasi-experimental research with pre and post test one goup design. The population was pre-menarche adolescent girls at SMP Negeri 3 Lubuk Pakam totaling 42 people and willing to be a sample of 34 people. BC Cangi nuggets were given for 15 days as much as 100 g (4 pieces) during school breaks. Before being analyzed, data normality test was conducted using Kolmogorov Smirnov, then T-dependent statistical test. Results: The results of the T-dependent statistical test showed that there was an effect of giving BC Cangi nuggets on IGF-1, albumin, zinc, and Hb levels (p-value=0.001) as well as zinc levels (p-value=0.005). BC Cangi nuggets contain high levels of protein, Fe, and zinc which play a role in activating the IGF-1, also contain albumin and protein to maintain the presence of zinc. Conclusions: The administration of BC Cangi nuggets to pre-menarche adolescent students had a significant effect on the increase in IGF-1, albumin, zinc, and hemoglobin levels.